The Construction of Work Readiness Scale - Wardani, Farenanda Kusuma; Isnain, Afifudin; Alifah, Anggi Nur; Khasanah, Putri Uswatun; Nabila, Farica Ayu; P, Shavira Ika; Astikawati, Hemalia; Husna, Aftina Nurul (Prosiding University Research Colloquium, 2021)
Fresh graduates are human resources that determine the sustainability of an organization/company. Psychologically, they should have mature work readiness before entering the world of work. This study aims to develop a work readiness scale for fresh graduates. Psychological work readiness is defined as the extent to which graduates are perceived to have the attitudes and attributes that make them ready to succeed in the work environment. This scale contains four aspects that support the form of self-readiness for the world of work, namely resilience/resilience, maturity/maturity, motivation, and interpersonal skills. Participants in this study were 61 fresh graduates of Bachelor and Diploma programs in all majors with a graduation period of 2019-2021 and not yet working. The data collection method used is the saturation sampling and snowball sampling technique. The data were analyzed for validity and tested for reliability with the SPSS program. Of the 72 items tested, 24 final items were obtained with an alpha reliability of 0.938 and showed good validity. The work readiness scale for fresh graduates has good psychometric properties and can be used for assessment and research.